Social involvement and park citizenship as moderators for quality-of-life in a national park - Ramkissoon, Haywantee; Mavondo, F.; Uysal, Muzaffer (Routledge, 2017)
This paper contributes to the advancement of quality-of-life research in tourism by examining complex relationships involving direct, mediated, moderated and moderated mediation relationships among the antecedents to quality-of-life. Using a sample of 222 repeat visitors in an Australian national park, the findings indicate positive significant effects of (1) place satisfaction on quality-of-life; (2) place satisfaction on place attachment; (3) place attachment on quality-of-life; (4) park citizenship on place attachment. The findings further support that (5) place attachment mediates the relationship between place satisfaction and quality-of-life; (6) social involvement moderates the relationship between place satisfaction and place attachment; (7) park citizenship moderates the relationship between place satisfaction and place attachment; (8) social involvement moderates the relationship between place attachment and quality-of-life; (9) social involvement moderates the indirect effect of place satisfaction on quality-of-life. Theoretical and practical implications are discussed. Park managers, for example, need to promote on-site marketing and post-visit communication/interpretation, encouraging repeat visits and behavioural change. Message delivery needs to promote a sense of belonging to the park with personal meaning, creating place distinctiveness. Personal actions to promote include signing petitions supporting the park's biodiversity, and other resources, and volunteering to participate in meetings and other direct actions.